Virgin and recently mated males are equally able to achieve new matings in Neoleucinodes elegantalis. (23rd September 2013) - PONTES, WENDEL J. TELES; CUNHA, ERIVELTON G.; ARAÚJO, HERNANE D.; BARROS, REGINALDO; LIMA, ERALDO
Abstract: Lepidopteran male mating success is recognized to be directly related to physical and behavioural traits such as ability, vigour, activity and persistence in courtship. In the tomato fruit borer Neoleucinodes elegantalis Guenée, the mating system is known to be monogamic and therefore males' sexual investment is apparently low. The hypothesis that recently mated males have a remating probability equal to that of virgin males is tested. The impact of body size in remating success and the cost of remating are also analyzed. Mated males show as much propensity to remate as naïve ones. Copula duration and the time taken to copulate are similar in mated and virgin males. However, spermatophore size is not related to male size. The results suggest the ability of N.   elegantalis males to remate within 24 h between mating events and their propensity to remate are not affected by copula investment. © 2013 The Royal Entomological Society